Marketing Entry Strategy for Kerberos into East German market - Volhejn, Jan (2024)
This thesis explores a strategic marketing entry plan for Kerberos Krematorium's expansion into the pet cremation market in Eastern Germany. Combining primary research in the form of a questionnaire with secondary data from industry reports, the study identifies target audience and its preferences, emphasizing the demand for personalized and eco-friendly services. The methodology involves detailed market segmentation and localization of services to align with regional tastes and regulatory standards. Additionally, a thorough competitor analysis was conducted, examining competitors' communication styles and philanthropic activities to inform Kerberos's marketing strategy. The marketing strategy leverages both traditional and digital channels, focusing on social media and community engagement to effectively reach and resonate with the target audience. By highlighting the compassionate, eco-friendly, and locally engaged approach of Kerberos, the strategy aims to position the company as a leading provider in the pet cremation industry. This thesis provides actionable insights for businesses seeking to navigate the complex and emotionally driven pet cremation market.